2016
DOI: 10.1128/jvi.01003-16
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Innate Immune DNA Sensor IFI16 Is Degraded during Lytic Reactivation of Kaposi's Sarcoma-Associated Herpesvirus (KSHV): Role of IFI16 in Maintenance of KSHV Latency

Abstract: IMPORTANCELike all herpesviruses, latency is an integral part of the life cycle of Kaposi's sarcoma-associated herpesvirus (KSHV), an etiological agent for many human cancers. Herpesviruses utilize viral and host factors to successfully evade the host immune system to maintain latency. Reactivation is a complex event where the latent episomal viral genome springs back to active transcription of lytic cycle genes. Our studies reveal that KSHV has evolved to utilize the innate immune sensor IFI16 to keep lytic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 91 publications
(159 reference statements)
4
75
1
Order By: Relevance
“…IFI16 is a restriction factor for several other DNA viruses, including HSV-1 and HCMV (Gariano et al, 2012; Orzalli et al, 2013), and it induces anti-viral inflammasome activity against KSHV and EBV (Ansari et al, 2013; Roy et al, 2016). However, while IFI16 restricts incoming HSV-1 DNA, it does not restrict SV40 DNA packaged in nucleosomes and delivered to the nucleus by transfection (Orzalli et al, 2013).…”
Section: Host Factors That Restrict Transcription and Replication mentioning
confidence: 99%
“…IFI16 is a restriction factor for several other DNA viruses, including HSV-1 and HCMV (Gariano et al, 2012; Orzalli et al, 2013), and it induces anti-viral inflammasome activity against KSHV and EBV (Ansari et al, 2013; Roy et al, 2016). However, while IFI16 restricts incoming HSV-1 DNA, it does not restrict SV40 DNA packaged in nucleosomes and delivered to the nucleus by transfection (Orzalli et al, 2013).…”
Section: Host Factors That Restrict Transcription and Replication mentioning
confidence: 99%
“…These data highlight again that, although PML-NBs and/or its components could be involved in the establishment and/or maintenance of herpesviral latency, it is unlikely that a common mechanism of interplay between PML-NBs and viral genomes during latency exists for all viruses. Intriguingly, a recent study on KSHV has suggested a role for IFI16 in maintenance of latent infection [105]. In summary, the potential role of known and yet to be discovered nuclear antiviral factors in latent infection is of major interest, and further studies are needed to understand how latency is established on incoming genomes.…”
Section: Possible Mechanisms For Distinct Cellular Responses: Detementioning
confidence: 99%
“…Furthermore, IFI16 has been shown to be involved in the induction of IFN-ÎČ production during KSHV de novo infection by targeting the IFI16-STING-IRF3 axis (Ansari et al, 2015). Very recently, Roy et al (2016) demonstrated that IFI16 binds to the lytic gene promoter and acts as a transcriptional repressor to maintain viral latency. Overall, these observations indicate that the efficient maintenance of latency by IFI16 and the activation of the IFI16 inflammasome by latent KSHV could drive KSHV-associated inflammatory cytokine syndromes, like MCD.…”
Section: The Cytosolic Dna Sensing Receptor Signaling Pathwaymentioning
confidence: 99%